NILAI PERSEPSIAN KONSUMEN PADA ROKOK KRETEK MILD MEREK LAMA DAN MEREK BARU STUDI PADA PELANGGAN ROKOK DI SURABAYA - , Bayu Yodhana Putra, Dr. BM. Purwanto, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is conducted to acquire empirical evidence related on consumer perceived value on Mild kretek cigarettes in the city of Surabaya. Sampling method selected is using purposive sampling method which obtained 120 respondents during January - mid March 2013 in the city of Surabaya on people who have been active smokers of Mild kretek cigarettes in the last three months. This research applies descriptive analysis and t test between the mean of old Mild group (A Mild, U Mild, LA Light and Class Mild) and new Mild group (X Mild, Djarum Super Mezzo, Pro Mild, Mild Neo, One Club Mild, Geo Mild, Mild Galan, and Uno Mild). From the test results, the old Mild group gained greater appreciation in perceptions related to social, emotional, and conditional aspects, while the new Mild group has greater appreciation in the functional perception. Epistemic perception is the only perception that is not significantly perceived by both groups. Meanwhile, the newcomer brand which yielded the highest appreciation by the respondents in Surabaya region is Pro Mild. This research contains limitation which is only conducted for Mild cigarette customers who are grouped into the new and old brand smoker groups. Furthermore, the other limitation is that the respondents should have smoked at least one of the brands in the groups for the last three months and the study area is limited to Surabaya.